Načrtovanje in izvajanje obravnave življenjskih prostorov v naravi - Rajšp, Martina; Pintarič, Nuša; Fošnarič, Samo (Revija za elementarno izobraževanje, 2013)
Planning and Performing Outdoor Living Space Lessons. The nature is man’s first teacher. Slovenian people are generally proud of their country being a green oasis in the middle of Europe, characterised by many natural and geographical features. As we were interested to see whether younger primary school students had experience with learning about such features in outdoor classes, we completed an empirical research on a sample of 84 primary school class teachers in the Prekmurje region. We investigated if teachers included field trips (and how many) in their lesson plans and how many of those they actually took their students to. We established that teachers (too) rarely allowed their students to gain knowledge and information directly from nature.